Losy pracowników niemieckiej gadzinówki „Nowy Kurier Warszawski” w świetle powojennych procesów z dekretu sierpniowego - Schnepf-Kołacz, Zuzanna (Zagłada Żydów. Studia i Materiały, 2006)
The main sources used in this article are investigation and court files of post-war trials of 15 former journalists of Nowy Kurier Warszawski, so-called “reptile newspaper” (gadzinówka), a newspaper published by German authorities in General Government throughout the entire occupation. They were charged and convicted of collaboration on the basis of the so-called “August decree” of the Polish Committee of National Liberation. The sentences in this trial were surprisingly low as compared with those of others tired for collaboration with the Germans, including many Home Army soldiers. Such trials were used by the communist government to eliminate political opponents in post-war Poland. In this article, the author considers whether the journalists' trials should also be treated as a political issue, and formulates a definition of collaboration, delineating its boundaries in the light of court rulings. The defendants' and witnesses' testimonies are used to present work conditions in Nowy Kurier Warszawski and methods of recruitment among the Poles. A reconstruction of the newspaper's employees' line of defence made it possible to determine the structure of this type of narration and confront it with the witnesses' testimonies, recollections of other journalists and documents of the Home Army, the Delegatura Rządu RP na Kraj (Government Delegate's Office at Home), as well as personal files of the Security Service (Służba Bezpieczeństwa, SB). Available materials made it possible to get acquainted with the post-war fate of the defendants and analyse what influence on their future lives had their work for the “reptile newspaper” (gadzinówka).